Assess the Cultural and Social Beliefs Regarding Pregnancy among Antenatal Mothers in Selected Hospital, Vadodara with View to Provide Information Booklet - R. Waghmare, Priyanka; Patel, Srushti; Patel, Trusha; Talapada, Harshad; Patel, Tanvi (International Journal of Psychosocial Rehabilitation, 2020)
Background: In spite of the bloom in health care facilities, maternal and fetal morbidity as well as mortality is the biggest concern in India. Cultural beliefs can influence women’s use of formal maternal health care services and induce threats towards maternal and fetal health. Hence it is important to know the various beliefs followed by childbearing women.Aim: Assess the cultural and social beliefs regarding pregnancy among antenatal mothers.Materials and Method: A descriptive research study was conducted among 60 antenatal mothers who were selected by using a non-probability sampling technique. The primary data of research collected through likert scale based on cultural and social belief during pregnancy Data was analyzed by descriptive and inferential statistics. The significance level of the study is fixed at the 0.05 level.Result: The result of the study shows that harmful beliefs regarding being pregnant are followed by 55% of antenatal mothers. 28.3% are following a moderately beneficial belief. Whereas, only 16.7% of antenatal mothers are following beneficial cultural and social beliefs regarding pregnancy. overall mean percentage of cultural and social belief of pregnancy (88.83%) with SD (19.58). The analysis of the association between a demographic variable and cultural and social belief of pregnancy was significantly associated with educational status, type of family, occupation, and source of information. However, other demographic variables, including age, area of residence, are not significantly associated with the cultural and social beliefs of pregnancy.Conclusion: In the present study it is evident that childbearing mothers are still following some belief that is not beneficial for healthy outcomes of pregnancy. This is a matter of concern that needs the counseling and evaluation of the views of the mother during reproductive age.